2019
DOI: 10.1007/s12668-019-00618-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetical Release Study of Copper Ferrite Nanoparticle Incorporated on PCL/Collagen Nanofiber for Naproxen Delivery

Abstract: Nanofiber has become one of tissue engineering examples and has extensive application on medical field, particularly as a wound healing and wound dressing. In this research, nanofiber composite based on polycaprolactone and collagen was successfully obtained via electrospinning process and further developed as host of naproxen as anti-inflammatory agents. Addition of copper ferrite (CuFe 2 O 4 ) nanoparticles on the nanocomposite becomes an advance part on this study to control of naproxen release. Several cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Moreover, Armedya et al also studied naproxen’s kinetic release from copper ferrite nanoparticles incorporated on PCL/collagen nanofiber. They reported that the release profile was fitted to the Korsmeyer-Peppas model and the release mechanism was a combination of Fickian diffusion and swelling [ 32 ]. Furthermore, Huo et al prepared PCL/collagen nanofibers containing artemisinin (ATR) for transdermal drug delivery system that showed the release of ART from the PCL/Col nanofibers followed the Korsmeyer-Peppas model.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Armedya et al also studied naproxen’s kinetic release from copper ferrite nanoparticles incorporated on PCL/collagen nanofiber. They reported that the release profile was fitted to the Korsmeyer-Peppas model and the release mechanism was a combination of Fickian diffusion and swelling [ 32 ]. Furthermore, Huo et al prepared PCL/collagen nanofibers containing artemisinin (ATR) for transdermal drug delivery system that showed the release of ART from the PCL/Col nanofibers followed the Korsmeyer-Peppas model.…”
Section: Resultsmentioning
confidence: 99%
“…The NAP concentration contained in the Fe 3 O 4 @CDs-NAP was calculated by matching the maximum absorbance of NAP with the original standard curve at 330.5 nm. 53 …”
Section: Methodsmentioning
confidence: 99%
“…It is well known that CDs exhibited excellent biocompatibility and non-toxic features. 68 In the nanohybrid design, even Fe 3 O 4 and other metal ferrites claimed also have low toxic effects; 52,53,69 CDs acting like a cover on the surface of magnetite nanoparticles would possibly prevent toxic reactions between the nanoparticles and the cellular system. Moreover, the half-maximal cytotoxic concentration (CC 50 ) of Fe 3 O 4 @CDs also supported this statement in proving the nontoxic property of the nanohybrid, even at a concentration as high as 17 671.5 ± 1742.6 mg mL −1 (showed on Fig.…”
Section: Cytotoxicity Evaluationmentioning
confidence: 99%
“…16 CA is also well-used in various applications because of its excellent mechanical properties and compatibility, such as in laminates, fiber adhesives, and films. 8,12,14,17 CA nanofibers also have high potential for use in bone regeneration, 18 gas sensors, 19 supercapacitors, 20 filtration, 21 and drug delivery. 22 The preparation of CA nanofibers using the coaxial electrospinning method has several advantages, such as the controlled and continuous release of drugs over a period and administration of multiple drugs.…”
Section: Introductionmentioning
confidence: 99%
“… 11 The characteristics, composition and formulation of the materials in wound dressings influence the effectiveness of wound healing. 12 Wound management systems containing drugs can act as drug delivery systems and affect the healing process precisely. Development of transdermal delivery systems took a big step forward by applying nanofibers to control drug movement and systemic delivery.…”
Section: Introductionmentioning
confidence: 99%